2002
DOI: 10.1075/pc.10.1-2.12tur
|View full text |Cite
|
Sign up to set email alerts
|

Body part terms in Kaytetye feeling expressions

Abstract: This paper addresses the question of how feelings are expressed in Kaytetye, a Central Australian language of the Pama-Nyugan family. It identifies three different formal constructions for expressing feelings, and explores the extent to which specific body part terms are associated with types of feelings, based on linguistic evidence in the form of lexical compounds, collocations and the way people talk about feelings. It is suggested that particular body part terms collocate with different feeling expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…East-Asians cultures are not the only non-Western cultural groups that exhibit this pattern. A growing number of recent studies has found that many cultural groups, including those from Papua New Guinea ( Lindström, 2002 ), aboriginal Australia ( Turpin, 2002 ), and West Africa ( Geurts, 2003 ) display a similar emphasis on the body. In the West African case, anthropologists have observed that cultural terms exist that refer exclusively to bodily sensations for which there is no English translation (e.g., “seselelame,” which can be roughly translated as “feel-feel-inside-the-body”— Geurts, 2003 ).…”
Section: Part 1: Cross-cultural Differences In Somatic Awareness and mentioning
confidence: 99%
“…East-Asians cultures are not the only non-Western cultural groups that exhibit this pattern. A growing number of recent studies has found that many cultural groups, including those from Papua New Guinea ( Lindström, 2002 ), aboriginal Australia ( Turpin, 2002 ), and West Africa ( Geurts, 2003 ) display a similar emphasis on the body. In the West African case, anthropologists have observed that cultural terms exist that refer exclusively to bodily sensations for which there is no English translation (e.g., “seselelame,” which can be roughly translated as “feel-feel-inside-the-body”— Geurts, 2003 ).…”
Section: Part 1: Cross-cultural Differences In Somatic Awareness and mentioning
confidence: 99%
“…It has long been recognized that there are cultural variations in the extent to which the body serves as a prime referent for emotion metaphors. For example, the frequent references to the body in the emotion metaphors have been identified in Chinese (Tung, 1984;Ye, 2002;Yu, 2002), Japanese (Hasada, 2002), West African (Ameka, 2002), Russian (Pavlenko, 2002), and Kaytetye (Turpin, 2002) languages. However, scholars differ in their opinions as to whether such semantic referents to the body may still be classified as emotions.…”
Section: Culture and Emotion Lexicamentioning
confidence: 99%
“…Huang (2002) describes a comparable usage in Tsou (Austronesian), with important differences. Turpin (2002) indicates that body-part words may also serve two distinct functions in Kaytetye (Central Australia, Pama-Nyungan, Arandic), but does not unfold the details of the phenomenon. Overall, very few authors have dedicated much attention to the descriptive functions of body-part nouns with respect to emotional behaviors, nor to the consequences of such descriptions for the emotion lexicon.…”
Section: Aim Of the Workmentioning
confidence: 99%
“…In her article on the use of body-part words in emotional constructions in Kaytetye, Turpin (2002) observes that in this language some emotions are primarily described by means of physical descriptions. Inspired by Peile (1997) and Myers (1986), she suggests that this may be explained by "a tendency to refer indirectly to emotional experience, [maybe] because people are more inclined to talk about things that can be perceived externally, rather than speculate on another person's internal feelings".…”
Section: Cultural Representations and Habitsmentioning
confidence: 99%